A case study of KELHELDEPT : The implications of medical officer doing administrative work - Mohamad Norazam Abdullah. (2015)
The purpose of this case study were to understand what are the implication emerge when Medical Officer at KELHELDEPT doing administrative work rather than practicing their medical skills to treat patient. This study tend to understand whether this action is threats or give a good implications to them organization.